2017
DOI: 10.1017/s0144686x1700068x
|View full text |Cite
|
Sign up to set email alerts
|

The intimate lives of older adults living with HIV: a qualitative study of the challenges associated with the intersection of HIV and ageing

Abstract: Older adults living with human immunodeficiency virus (HIV) are at risk of experiencing difficulties in their intimate lives due to the combined effects of HIV and ageing. To date, little research has focused on the lived experience of sexuality. This article seeks to fill in the gap by documenting the challenges faced by this population with respect to their intimate relationships and sexual lives. Based upon the results of a qualitative study conducted in Montreal (2010–2012) using semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
(101 reference statements)
1
3
0
Order By: Relevance
“…This also made establishing sexual or romantic relationships difficult, a challenge associated with ageing and HIV. Recent research has highlighted how ageism and HIV stigma can have negative repercussions on the lives of older persons living with HIV (Wallach and Brotman, 2018), and our research extends this work to demonstrate the additional impact of homonegativity faced by many older adults living with HIV and the challenges of contending with such stigmas in rural communities.…”
Section: Discussionsupporting
confidence: 61%
“…This also made establishing sexual or romantic relationships difficult, a challenge associated with ageing and HIV. Recent research has highlighted how ageism and HIV stigma can have negative repercussions on the lives of older persons living with HIV (Wallach and Brotman, 2018), and our research extends this work to demonstrate the additional impact of homonegativity faced by many older adults living with HIV and the challenges of contending with such stigmas in rural communities.…”
Section: Discussionsupporting
confidence: 61%
“…Despite deficiencies in population-level data collections, over the past decade there has been a growing gerontological evidence base of the unique ageing experience of LGBTQI people. Within Ageing & Society, studies focusing upon LGBTQI ageing have investigated deficiencies and best practices in aged care (Willis et al, 2016;Leyerzapf et al, 2018;Hafford-Letchfield et al, 2023), use of health and social care services (Kneale et al, 2021;Benbow et al, 2022), social capital and social support (Cronin and King, 2014;Hughes, 2016;Hawthorne et al, 2020), inequalities, attitudes and discrimination (Simpson et al, 2018;Bécares, 2021;Lyons et al, 2021), as well as exploring issues of ageing with an LGBTQI identity (Lyons et al, 2015;Bower et al, 2021;Willis et al, 2021), including those with specific health conditions such as dementia or HIV (Price, 2012;Wallach and Brotman, 2018). These research priorities mirror themes in LGBTQI ageing more generally (Fredriksen-Goldsen and Muraco, 2010;Hawthorne et al, 2020;Kneale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Social science research has also revealed the many psychosocial difficulties experienced by older adults living with HIV (OAHIV). [5][6][7][8][9] Older adults living with HIV (OAHIV) are particularly vulnerable to mental health problems, 4,10,11 isolation, 5,12 and HIV and age-related stigma 1 . 8,12,13 In addition, OAHIV often find themselves confronted by a lack of emotional and instrumental support from the community due to distance from family and the absence of intimate partners.…”
Section: Introductionmentioning
confidence: 99%